Hubungan Keterlibatan Guru dalam Pertemuan Kelompok Kerja Guru (KKG) dengan Keterampilan dalam Melaksanakan Prosedur Mengajar - Bambang Budi Wiyono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This study aimed to investigate correlation between teacher meeting in teacher supervision organization (KKG) and teachers' teaching competence. It was conducted in public elementary schools in Singosari Malang. The sampel consisted of 48 teachers of 20 public elementary schools taken by cluster proporsional random sampling. The data was collected by questionnaires and observation. The result showed that there was correlation between teachers participation in the meeting and their competence. All activities in the teachers meeting have correlation with teaching competence of teachers.